Impact of Coleman Block Test on Adult Hindfoot Alignment Assessed by Clinical Examination, Radiography, and Weight-Bearing Computed Tomography. Issue 3 (29th July 2020) - Foran, Ian M.; Mehraban, Nasima; Jacobsen, Stephen K.; Bohl, Daniel D.; Lin, Johnny; Hamid, Kamran S.; Lee, Simon
Background: Cavovarus foot constitutes a complex 3-dimensional deformity. The Coleman block test has traditionally been used to distinguish between forefoot- and hindfoot-driven deformity. However, there has been no objective evaluation of the Coleman block test using radiographs or weightbearing computed tomography (WBCT). The purpose of this study was to compare hindfoot alignment in adult cavovarus feet with and without the Coleman block using clinical examination, radiography, and WBCT. Methods: Six feet in 6 patients with a clinical diagnosis of cavovarus foot deformity were prospectively enrolled. All feet underwent clinical photography with the camera positioned at 0 degrees to the heel, hindfoot alignment view radiography with the beam positioned 20 degrees off the ground, and WBCT, both with and without the Coleman block in place. Clinical photos were characterized using the standing talocalcaneal angle (STCA), radiographs were characterized using the hindfoot alignment angle (HAA), and WBCTs were characterized using manual and automated hindfoot alignment angle (HAA) and foot and ankle offset (FAO). Using paired analyses, measurements taken with the Coleman block in place were compared to those taken without the Coleman block. Finally, the different methods of measuring hindfoot alignment were tested for correlation with each other. Mean age was 56 years (range 38-69). Results: On clinical photography, the STCA decreased by 3.8 degrees with addition of the block (from 10.0±6.6 degrees varus without block to 6.2±7.1 degrees varus with block; P = .001). On radiograph, HAA decreased by 9.0 degrees with addition of the block (from 16.8±8.4 degrees varus without block to 7.5±6.3 degrees varus with block; P = .07). On WBCT, hindfoot alignment angle changed an average of 3.2 degrees (33.4 degrees varus without block, 30.2 degrees varus with block; P = .008). On WBCT, FAO decreased by 1.4% (from 11.3% varus without block to 10.1% varus with block; P = .003). Clinical examination and automated WBCT measurements were strongly correlated with each other. Conclusion: Clinical examination, radiograph, and WBCT demonstrated improvements in hindfoot varus using the Coleman block test in adults, but no patient demonstrated complete resolution of deformity regardless of the measurement modality. Clinical examination correlated strongly with automated WBCT measurements. Level of Evidence: Level IV, retrospective case review.